RELATIONSHIP BETWEEN AMIR TEMUR AND AMIR HUSSEIN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
We all know that in the 50s and 60s of the 14th century, Movarounnahr was divided into about 10 independent principalities. The rulers there declare themselves absolute rulers. Each province in the country is divided into separate administrations, which escalate into bloody wars. Political disunity, civil war, and strife led to economic hardship and devastation of the countrys population, especially the peasantry. In such a situation, a great power was maturing. This was the period when Amir Temur entered the political arena. In addition, the position of Amir Hussein was much higher. In this article, I will elaborate on the relationship between the two great personalities above and the causes of the conflicts between them.